Effect of Selected Environmental Factors on the Microbicidal Effectiveness of Radiant Catalytic Ionization - Skowron, Krzysztof; Wałecka-Zacharska, Ewa; Grudlewska, Katarzyna; Kwiecińska-Piróg, Joanna; Wiktorczyk, Natalia; Kowalska, Maria; Paluszak, Zbigniew; Kosek-Paszkowska, Katarzyna; Brożek, Klaudia; Korkus, Jakub; Gospodarek-Komkowska, Eugenia (Frontiers in Microbiology, 2020)
The aim of this study was the assessment of the effect of time exposure, temperature, distance, and organic contaminants on radiant catalytic ionization (RCI) microbicidal effectiveness. The number of all examined bacteria decreased together with time exposure of RCI. The lowest recovery was obtained, both from the rubber surface (6.36 log CFU × cm-2) and steel (6.04 log CFU × cm-2) in the case of Escherichia coli O157:H7. On the other hand, Staphylococcus aureus was isolated in the largest number (rubber: 7.88 log CFU × cm-2, steel: 7.79 log CFU × cm-2). Among the tested environmental conditions, the greatest bacterial population was re-isolated at 4ºC (distance: 0.5 m, time: 24 h), whereas the lowest population was found at a distance of 0.5 m (temperature: 20ºC, time: 24 h) and on surfaces without contamination. In the samples treated with RCI, the bacterial population was the lowest on not contaminated surfaces, ranging from 3.76 log CFU × cm-2 (E. coli O157:H7) to 5.58 log CFU × cm-2 (S. aureus) for the rubber and from 3.26 log CFU × cm-2 (E. coli O157:H7) to 5.20 log CFU × cm-2 (S. aureus) for the stainless steel. The highest bacteria number was isolated from surfaces contaminated with meat and fish pulp. The lowest bacterial reduction caused by RCI, was found in the case of rubber contaminated with meat-fish pulp (24 h, 0.5 m, 20ºC). The reduction rate was equal to 0.89 log CFU × cm-2 for S. aureus, 1.17 log CFU × cm-2 for Listeria monocytogenes, 1.43 log CFU × cm-2 for Salmonella Enteritidis and 1.61 log CFU × cm-2 for E. coli O157:H7. In turn, the greatest bacterial reduction was found in the case of not contaminated steel (24 h, 0.5 m, 37ºC). The reduction rate was equal to 4.52 log CFU × cm-2 for L. monocytogenes, 3.61 log CFU × cm-2 for S. Enteritidis, 2.98 log CFU × cm-2 for E. coli O157:H7 and 2.77 log CFU × cm-2 for S. aureus. RCI allows the inactivation of pathogens from stainless steel and rubber surfaces. Its efficacy is species-dependent and affected by environmental factors.